2014
DOI: 10.18632/genesandcancer.16
|View full text |Cite
|
Sign up to set email alerts
|

HOXA10 is associated with temozolomide resistance through regulation of the homologous recombinant DNA repair pathway in glioblastoma cell lines

Abstract: ABSTRACT:Temozolomide resistance is associated with multiple DNA repair pathways. We investigated homeobox (HOX) genes for their role in temozolomide resistance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…In the present study we sought to elucidate underlying molecular mechanisms triggering the inappropriate expression of a HOX-signature. Such a HOX gene dominated expression signature has been associated by others, and us with resistance to temozolomide and conferring of glioma-initiating properties [ 7 , 8 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study we sought to elucidate underlying molecular mechanisms triggering the inappropriate expression of a HOX-signature. Such a HOX gene dominated expression signature has been associated by others, and us with resistance to temozolomide and conferring of glioma-initiating properties [ 7 , 8 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal expression of a HOX gene signature has been confirmed recently in GICs, where it has been functionally associated with their glioma initiating potential [ 8 ]. The importance of HOX gene expression for gliomagenesis and treatment resistance to temozolomide has been emphasized in several studies [ 8 - 12 ]. In 2006, Krivtsov and colleagues first described the inappropriate expression of a HOX gene signature in acute myeloid leukemia (AML) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since several genes are reportedly involved in TMZ resistance, we investigated whether PLD1 affects the expression of TMZ resistance factors in GSCs. Interestingly, PLD1 depletion, but not TMZ treatment, markedly suppressed the expression of several TMZ resistance factors ( MGMT , ABCB1 , ABCG2 , PHF6 , MMP16 , and MCL1 ), but not HOXA9 and HOXA10 [26–30], in non‐sorted GSC‐X01 (Figure 4A). TMZ treatment and PLD1 depletion further suppressed the expression of the TMZ resistance factors.…”
Section: Resultsmentioning
confidence: 99%
“…EGR1 is a Cys2-His2-type zinc finger transcription factor that in GB cell lines has been shown to bind to GC-rich sites of the TGF-β promotor leading to decreased proliferation and suppressing transformation [68]. In contrast, another study showed that EGR1 induces U251 cell migration via activation of fibronectin [69]; and other reports indicated that EGR1 confers temozolomide resistance in GB [70,71]. EGR1 has also been shown to promote a glioma stem cell-like phenotype [72,73].…”
Section: Discussionmentioning
confidence: 99%